Regional collaborative quality improvement for trauma reduces complications and costs. Issue 1 (January 2015) - Hemmila, Mark R.; Cain-Nielsen, Anne H.; Wahl, Wendy L.; Vander Kolk, Wayne E.; Jakubus, Jill L.; Mikhail, Judy N.; Birkmeyer, Nancy J.
Abstract : BACKGROUND: Although evidence suggests that quality improvement to reduce complications for trauma patients should decrease costs, studies have not addressed this question directly. In Michigan, trauma centers and a private payer have created a regional collaborative quality initiative (CQI). This CQI program began as a pilot in 2008 and expanded to a formal statewide program in 2010. We examined the relationship between outcomes and expenditures for trauma patients treated in collaborative participant and nonparticipant hospitals. METHODS: Payer claims and collaborative registry data were analyzed for 30-day episode payments and serious complications in patients admitted with trauma diagnoses. Patients were categorized as treated in hospitals that had different CQI status: (1) never participated (Never-CQI); (2) collaborative participant, but patient treated before CQI initiation (Pre-CQI); or (3) active collaborative participant (Post-CQI). DRG International Classification of Diseases—9th Rev. codes were crosswalked to Abbreviated Injury Scale (AIS) 2005 codes. Episode payment data were risk adjusted (age, sex, comorbidities, type/severity of injury, and year of treatment), and price was standardized. Outcome data were risk adjusted. A serious complication consisted of one or more of the following occurrences: acute lung injury/adult respiratory distress syndrome, acute kidney injury, cardiac arrest with cardiopulmonary resuscitation, decubitus ulcer, deep vein thrombosis, enterocutaneous fistula, extremity compartment syndrome, mortality, myocardial infarction, pneumonia, pulmonary embolism, severe sepsis, stroke/cerebral vascular accident, unplanned intubation, or unplanned return to operating room. RESULTS: The risk-adjusted rate of serious complications declined from 14.9% to 9.1% ( p < 0.001) in participating hospitals (Post-CQI, n = 26). Average episode payments decreased by $2, 720 (from $36, 043 to $33, 323, p = 0.08) among patients treated in Post-CQI centers, whereas patients treated at Never-CQI institutions had a significant year-to-year increase in payments (from $23, 547 to $28, 446, p < 0.001). A savings of $6.5 million in total episode payments from 2010 to 2011 was achieved for payer-covered Post-CQI treated patients. CONCLUSION: This study confirms our hypothesis that participation in a regional CQI program improves outcomes and reduces costs for trauma patients. Support of a regional CQI for trauma represents an effective investment to achieve health care value. LEVEL OF EVIDENCE: Economic/value-based evaluation, level III. Abstract : Supplemental digital content is available in the article.